The Actual Problems of Modern Linguistics - Toshova Fayoza Nuriddinovna (Zien Journals, 2023)
This article describes thoroughly the actual problems of linguistics, the utmost possible study of linguistic and speech phenomena, the relationship of linguistics with various disciplines, the priorities of the organization of higher education
Keywords: linguistics; language; automatic indexing; modern linguistics